2013
DOI: 10.12659/msm.883786
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of pyelocalyceal dilation diagnosed by postnatal ultrasonographic screening of the urinary tract

Abstract: BackgroundUltrasonographic (US) screening of the urinary tract (UT) in infants was used to determine if there is a connection between the frequency of pyelocaliceal dilation (PCD) in asymptomatic infants with normal antenatal US screening and occurrence of congenital anomalies of kidney and urinary tract (CAKUT) and urinary tract infections (UTI).Material/MethodsUS screening of the UT was performed on 1000 healthy infants, 7 days to 6 months old. Two subgroups of kidneys were described: subgroup 1 contained ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For this purpose, the urinary system is screened prenatally, and cases with CAKUT are followed up with postnatal ultrasonography. However, it is known that some cases of CAKUT cannot be detected using prenatal USG due to technical and physiological reasons [9,13,21,22]. In the few studies investigating the prevalence of CACUT with postnatal USG, there was no standardized screening period; screening was performed over a wide time interval from three days to six months and a CACUT prevalence of 1.5% to 7.4% was reported [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, the urinary system is screened prenatally, and cases with CAKUT are followed up with postnatal ultrasonography. However, it is known that some cases of CAKUT cannot be detected using prenatal USG due to technical and physiological reasons [9,13,21,22]. In the few studies investigating the prevalence of CACUT with postnatal USG, there was no standardized screening period; screening was performed over a wide time interval from three days to six months and a CACUT prevalence of 1.5% to 7.4% was reported [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, thirty-two cases of hydronephrosis were detected via postnatal USG, as well as three cases of renal agenesis, four cases of horseshoe kidney, one case of MCDK, and two cases of duplex systems that could not be detected using prenatal USG. Drnasin et al [21] reported the prevalence of hydronephrosis as 7.4% in a postnatal study of 1000 healthy infants screened with prenatal USG and reported as "normal". Miyakita et al [11] reported that 39% of 92 cases of hydronephrosis were detected in the prenatal period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation